PENGARUH PENGGUNAAN MODEL PEMBELAJARAN ACTIVE LEARNING TERHADAP MINAT BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA KRISTEN, DI UKRIM YOGYAKARTA - Evi Tobeli (Universitas Kristen Immanuel, 2019)
Active learning model is a conceptual that contains planning of learning that will be implemented as a procedure in learning by involving students so that they are enthusiastic in learning and have learning experinces and achieve learning goals. The indicators of active learning models in this study are cooperative learning models and contextual learning models (CTL). Student learning interest is a tendency or sense of interest in student learning can be developed through the creativity of an educator with varied in the use of teaching methods and learning steps. Indicators of interest in learning in this study are attention feelings and motives